Ibu Kreatif, Keluarga Produktif: Pemberdayaan Perempuan melalui Pemanfaatan Potensi Lokal dan Pemasaran Digital untuk Penguatan Ekonomi Keluarga di Desa Muntal, Gunungpati, Semarang - Risma Nurhapsari; Erlinda Sholihah; Lukman Santoso; Dani Sasmoko; Aftuqa Sholikatur Rohmania (Fokus ABDIMAS, 2026)
Women play an important role in strengthening household economic resilience; however, their potential is often not optimally utilized for productive economic activities. This condition was also identified among members of the PKK organization in Muntal Village, Patemon Subdistrict, Gunungpati District, Semarang City, who possess various local resources that can be developed into family-based business opportunities. Nevertheless, limited knowledge regarding local resource utilization, digital marketing, and business financial management has become a barrier to entrepreneurial development. This community service program aimed to enhance the capacity of PKK members through the utilization of local potential and digital marketing to strengthen family economic productivity. The program employed a participatory approach involving participants in needs assessment, educational sessions, interactive discussions, digital marketing training, and simple financial management assistance. The results demonstrated an improvement in participants’ understanding of local resource-based business opportunities, product innovation, social media marketing, and basic financial record-keeping. Furthermore, the program increased entrepreneurial motivation and self-confidence among participants to initiate and develop family-based businesses. The activity contributed positively to strengthening the role of women as drivers of family economic development and creating opportunities for sustainable micro-enterprise growth within the community. Therefore, women's empowerment through entrepreneurial capacity building and digital literacy can serve as an effective strategy for improving family economic independence and community welfare.